2020
DOI: 10.1155/2020/1874570
|View full text |Cite
|
Sign up to set email alerts
|

Fecal Microbiota Transplantation for Clostridioides Difficile Infection in Patients with Chronic Liver Disease

Abstract: Background. Fecal microbiota transplantation (FMT) is a well-established therapeutic option for patients with antibiotic resistant Clostridioides difficile infection (CDI). However, the efficacy of FMT in patients with chronic liver disease remains elusive. Aims. We studied the effect of FMT on chronic liver disease (CLD) patients with CDI at our tertiary medical center. Methods. A cohort of all patients who received FMT from December 2012 to May 2014 for refractory or recurrent CDI was identified. Patients we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
15
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(15 citation statements)
references
References 32 publications
0
15
0
Order By: Relevance
“…In another series, of which 9 patients had cirrhosis, there was no significant worsening of Child-Pugh scores after FMT, though specific data about adverse events was not tabulated. 32 Specific AE data were collected by Bajaj and colleagues in a phase 1, randomized, placebo-controlled trial of FMT for HE. 33 In this study, SAEs (defined as hospitalizations and emergency room visits) occurred in 6/10 patients who received placebo, and only 1/10 patients who received FMT.…”
Section: Discussionmentioning
confidence: 99%
“…In another series, of which 9 patients had cirrhosis, there was no significant worsening of Child-Pugh scores after FMT, though specific data about adverse events was not tabulated. 32 Specific AE data were collected by Bajaj and colleagues in a phase 1, randomized, placebo-controlled trial of FMT for HE. 33 In this study, SAEs (defined as hospitalizations and emergency room visits) occurred in 6/10 patients who received placebo, and only 1/10 patients who received FMT.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, it has been successfully used to treat concomitant C. difficile. [84][85][86] Several more studies are being planned or are in process to leverage this exciting approach. 87 Most current studies are small-scale, illustrating the first important step of any investigation, i.e.…”
Section: Key Pointsmentioning
confidence: 99%
“…A study including cirrhotic patients, aiming to assess safety, tolerability and impact on microbiota and brain function in hepatic encephalopathy of capsulated FMT, demonstrated that oral FMT capsules appear to be safe, and even improved EncephalApp performance [90]. Another study including patients with chronic liver disease, among which 9 with cirrhosis and 1 recipient of liver transplantation, FMT was well tolerated, without infectious complications [91].…”
Section: What Recipient Factors Influence the Outcome Of Fmt When Trementioning
confidence: 99%